The naughtiest girl is a monitor - Blyton, Enid (Hodder London, 1999)
When Elizabeth Allen is chosen to be a school monitor, she's delighted. But she soon finds out what a responsible job it is. The harder she tries, the worse she behaves! Will the naughtiest girl in the school ever learn to be good?